Bioactive molecules from haloarchaea: Scope and prospects for industrial and therapeutic applications - Moopantakath, Jamseel; Imchen, Madangchanok; Anju, V. T.; Busi, Siddhardha; Dyavaiah, Madhu; Martínez-Espinosa, Rosa María; Kumavath, Ranjith (Frontiers in Microbiology, 2023)
Marine environments and salty inland ecosystems encompass various environmental conditions, such as extremes of temperature, salinity, pH, pressure, altitude, dry conditions, and nutrient scarcity. The extremely halophilic archaea (also called haloarchaea) are a group of microorganisms requiring high salt concentrations (2-6 M NaCl) for optimal growth. Haloarchaea have different metabolic adaptations to withstand these extreme conditions. Among the adaptations, several vesicles, granules, primary and secondary metabolites are produced that are highly significant in biotechnology, such as carotenoids, halocins, enzymes, and granules of polyhydroxyalkanoates (PHAs). Among halophilic enzymes, reductases play a significant role in the textile industry and the degradation of hydrocarbon compounds. Enzymes like dehydrogenases, glycosyl hydrolases, lipases, esterases, and proteases can also be used in several industrial procedures. More recently, several studies stated that carotenoids, gas vacuoles, and liposomes produced by haloarchaea have specific applications in medicine and pharmacy. Additionally, the production of biodegradable and biocompatible polymers by haloarchaea to store carbon makes them potent candidates to be used as cell factories in the industrial production of bioplastics. Furthermore, some haloarchaeal species can synthesise nanoparticles during heavy metal detoxification, thus shedding light on a new approach to producing nanoparticles on a large scale. Recent studies also highlight that exopolysaccharides from haloarchaea can bind the SARS-CoV-2 spike protein. This review explores the potential of haloarchaea in the industry and biotechnology as cellular factories to upscale the production of diverse bioactive compounds.